Harga Pokok Produksi dalam Kaitannya dengan Penentuan Harga Jual untuk Pencapaian Target Laba Analisis (Studi Kasus pada PT. Indra Brothers di Bandar Lampung) - Chairul Anwar; Lidia Fasi Ashari; Indrayenti INDRAYENTI (Jurnal Akuntansi dan Keuangan, 2010)
The purpose of this study was to determine the cost of production calculation is applied to the PT. Brother's senses and its effect on the determination of the selling price of the company, and the study is expected to be useful as a conceptual contribution to the company in conducting its business activities and for determining policies for the betterment of the company, particularly regarding the determination and the determination of cost of production in relation to the determination of the selling price.Based on the above problems posed hypothesis, namely: "Calculation of Cost of Production is carried out by PT. Indra Brother's has not been implemented properly as the basis for determining the selling price. "In analyzing the problems used tool for qualitative and quantitative analysis. In the approach used to analyze the qualitative theory related to the cost of production and the theory used to analyze quantitative calculation of the cost of production and selling price. Based on the analysis it can be concluded that during the PT. Brother's senses in relation to determining the selling price has not appropriately allocate production costs which companies should take into account the elements of the ending inventory of raw material costs in the calculation of the cost of production. Miscalculation of the cost of production of the company could result in the selling price of the products is higher than the selling price of similar companies. Thus, it can be concluded that the calculation of cost of production and selling price of the products produced by the company is not yet right.